A Healthy Rhythm of Rest: Why a Sound Theology and Spiritual Praxis of Rest Matters to Life and Ministry - Richard Peck Woon (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2020)
Abstract. The article is for full-time Christian professionals to consider the importance of constructing a sound theology and spiritual praxis of rest in the context of life experience and practical ministry. It seeks to answer two critical questions from the perspective of the Sabbath,